Unveiling dimensions of organizational culture: an exploratory study in Malaysian R&D organizations - Asmawi, Arnifa; Mohan, Avvari V. (WILEY-BLACKWELL, 2011)
Previous literature indicated that research and development (R&D) activities are influenced, to a large extent, by the culture of the organization. While these studies have identified elements of culture that are conducive to R&D, identifying the existing dimensions of organizational culture in Malaysian R&D organizations has not been empirically explored. The measures for this study were originally developed for the sole purpose of capturing cultural aspects in R&D organizations in the Malaysian context. These measures were developed based on the relevant issues discovered from exploratory case studies and nine categories of cultural values identified from the literature. A sample of employees (n = 198) from 45 R&D organizations took part in this study. Factor analysis was adopted to uncover common underlying dimensions (factors) of the organizational culture construct. The findings suggest that the organizational culture construct in R&D organizations may best be represented through a structure of eight factors. The eight factors are teamwork and knowledge sharing, empowerment and recognition, conformity and impediments to R&D, risk-taking, customer orientation, autonomy, social networking, and organizational design. Despite some methodological issues that arose from this study, this model has the potential to become a management instrument to measure the underlying culture in R&D organizations. R&D managers can deploy this model to establish the baseline level of research culture in their respective units and thus provide the foundation for management initiatives to drive R&D activities. This model can also be used as benchmarking parameters when an R&D organization intends to evaluate various aspects of their organizational culture in relation to others that are considered to be leaders in the industry.